2019
DOI: 10.20961/stjssa.v16i2.30190
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Residual Effect of Zeolite and Manure on Alfisols Cation Exchange Capacity and Green Bean Yield

Abstract: <p>Nowadays the innovations in organic agriculture systems continue to be developed to achieve a sustainable agriculture system. In Indonesia with high rainfall, nutrient loss is still a major problem. The application of zeolite and manure as a soil amendment is expected to increase nutrients available in soil and cation exchange capacity of the soil in the long term. The results on the first planting season showed a significant increase in chemical soil fertility. The objective of this study is to resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…Ravali et al [ 54 ] observed around a 30% increase in CEC of a sandy loam after addition of 7.5 t/ha zeolite. Fudlel et al [ 55 ] reported the positive effect of 5 t/ha zeolite on CEC of an Alfisol. Chomczynska et al [ 56 ] observed around a 20% increase in CEC after 1%w/w zeolite addition to two degraded soils (edge of sand mine excavation and the fallow land).…”
Section: Resultsmentioning
confidence: 99%
“…Ravali et al [ 54 ] observed around a 30% increase in CEC of a sandy loam after addition of 7.5 t/ha zeolite. Fudlel et al [ 55 ] reported the positive effect of 5 t/ha zeolite on CEC of an Alfisol. Chomczynska et al [ 56 ] observed around a 20% increase in CEC after 1%w/w zeolite addition to two degraded soils (edge of sand mine excavation and the fallow land).…”
Section: Resultsmentioning
confidence: 99%
“…Zeolite media is good to use as a planting medium because it is stable and does not easily change or be damaged by water spray (Sangeetha and Baskar 2016). Zeolite is a mineral that can improve soil and plant productivity because it is alkaline, so that it can neutralize acidic soils, reduce the power of P fixation by soil colloids, increase CEC, and increase the activity of microorganisms in the soil (Jakkula and Wani, 2018;Kurniawan et al, 2019;Lajszner et al, 2018;Aainaa et al, 2018;Fudlel et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Inhomogeneous materials hamper a mechanistic description of diffusion processes, as only overall diffusion rates for the bulk material are determined [54]. Pores filled with water enhance diffusion within the material, but important for mass transfer is not only the total porosity, but also the structure of the pore network e.g., dead ends and surface area [55], linkage between the pores [56]. A higher influence on such processes by the shape of pores than their sizes was found by Al-Raoush [57].…”
Section: Mass-transfer Processesmentioning
confidence: 99%